Spectrophotometric method for simultaneous estimation of atenolol in combination with losartan potassium and hydrochlorothiazide in bulk and tablet formulation - Sanjay Bari; Shital Sathe; Pritam Jain; Sanjay Surana (Wolters Kluwer Medknow Publications, 2010)
Aim : To develop a simple, accurate, rapid and precise UV spectrophotometric method for the estimation of atenolol in combination with losartan potassium and hydrochlorothiazide. Materials and Methods : The method employs formation and solving simultaneous equation using 251.60 nm and 224.20 nm for losartan potassium and atenolol, 224.20 and 271.60 for atenolol and hydrochlorothiazide as two analytical wavelengths, using methanol water as a solvent. Results and Conclusion : The linearity was observed in the concentration range of 5-30 μg/ml (r=0.9991) for losratan pottassium, 2 - 12 μg/ml (r = 0.9995) for atenolol and 2 - 14 μg/ml (r = 0.9993) for hydrochlorothiazide. The results of the method were validated statistically and by recovery studies.